Flavonoids and fibrate modulate apoE4-induced processing of amyloid precursor protein in neuroblastoma cells - Davra, Viralkumar; Benzeroual, Kenza E. (Frontiers in Neuroscience, 2023)
Introduction Apolipoprotein (apo) E4, being a major genetic risk factor for Alzheimer’s disease (AD), is actively involved in the proteolytic processing of amyloid precursor protein (APP) to amyloid β (Aβ) peptide, the principle constituent of amyloid plaques in Alzheimer Disease (AD) patients. ApoE4 is believed to affect APP processing through intracellular cholesterol homeostasis, whereas lowering the cholesterol level by pharmacological agents has been suggested to reduce Aβ production. This study has investigated the effects of hypolipidemic agents fenofibrate, and the flavonoids–naringenin and diosmetin–on apoE4-induced APP processing in rat neuroblastoma cells stably transfected with human wild-type APP 695 (B103-hAPP695wt). Results B103-hAPP695wt cells were pretreated with different doses of flavonoids and fenofibrate for 1 h prior to apoE4 exposure for 24 h. ApoE4-induced production of intra- and extracellular Aβ peptides has been reduced with fenofibrate, naringenin, and diosmetin treatments. Pretreatment with diosmetin has significantly reduced apoE4-induced full-length APP (fl- APP) expression, whereas naringenin and fenofibrate had no effect on it. In addition, the increase in the apoE4-induced secretion of sAPPtotal and sAPPα has been dose-dependently reduced with drug pretreatment. On the other hand, the decrease in the expression of both APP-carboxy terminal fragments (CTF)-α and –β (generated by the α- or β-secretase cleavage of APP) by apoE4 was dose-dependently increased in cells pretreated with fenofibrate and naringenin but not diosmetin. Conclusion Thus, we suggest that fenofibrate, naringenin, and diosmetin treatments can reduce apoE4- induced Aβ production by distinct mechanisms that may prove useful in developing drugs for AD patients.